Antenatal Kratom Exposure: Literature Review and Clinical Management Recommendations - Ordean A (Dove Medical Press, 2023)
Alice Ordean1,2 1Department of Family and Community Medicine, University of Toronto, Toronto, Ontario, Canada; 2Department of Family Medicine, St. Joseph's Health Centre, Unity Health Toronto, Toronto, Ontario, CanadaCorrespondence: Alice Ordean, St. Joseph's Health Centre, Family Medicine Clinic, 30 The Queensway, Toronto, Ontario, M9A 1E6, Canada, Tel +1 416 530-6860, Fax +1 416 530-6160, Email alice.ordean@unityhealth.toAbstract: In recent years, there has been a rapid interest in using kratom for the self-management of various chronic pain, anxiety and mood conditions, as well as, for the management of opioid withdrawal symptoms. The two main kratom alkaloids have stimulant and opioid-like effects that cause concerns during pregnancy. A literature review was conducted, and ten case reports relating to maternal kratom use were included consisting of 12 mother-infant dyads. Case reports indicated that regular use of kratom was associated with the presence of maternal kratom dependence and withdrawal. The route and amount of kratom use reported was highly variable. The majority of women were only identified in the postpartum period after infants displayed symptoms and signs of neonatal withdrawal. Management of maternal kratom use varied and included either opioid agonist treatment with buprenorphine or morphine or detoxification. Most of the exposed infants were described to develop neonatal abstinence syndrome and more than half required pharmacological treatment with morphine. All neonates were discharged home in the care of their mothers. Clinicians should be aware of the possible clinical effects of perinatal kratom exposure and be able to implement appropriate maternal and neonatal management strategies.Keywords: Mitragyna, pregnancy, opioids, neonatal abstinence syndrome, opioid agonist treatment